The Effect of Realistic Mathematics Education Approach on Mathematical Problem Solving Ability - Reri Seprina Anggraini; Ahmad Fauzan (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2020)
Abstract. The improvement of mathematical problem-solving ability was the aim of this study through the application of the Realistic Mathematics Education approach compared to conventional learning according to the students' self-efficacy level. This study used a quasi-experimental study with a static group design conducted in eighth-grade students at SMP Negeri 1 Kerinci and SMP Negeri 5 Kerinci. Data collected through the questionnaire to determine students’ self-efficacy level and the test of students’ mathematical problem-solving abilities. The hypothesizes was tested using a t-test. The results showed that students’ mathematical problem-solving abilities who learned using the RME approach were higher than students’ abilities who learned using conventional learning. In addition, the mathematical problem-solving abilities of students who have low self-efficacy who learned using the RME approach were higher than those who learned using conventional learning. Abstrak. Peningkatan kemampuan pemecahan masalah matematis menjadi tujuan penelitian ini melalui penerapan pendekatan Realistic Mathematics Education (RME) yang dibandingkan dengan kelas yang menerapkan pembelajaran konvensional menurut tingkat self-efficacy siswa. Penelitian ini menggunakan penelitian kuasi eksperimen dengan desain static group design yang dilaksanakan di kelas VIII pada SMP Negeri 1 Kerinci dan SMP Negeri 5 Kerinci. Data dikumpulkan melalui angket untuk menentukan tingkat self-efficacy dan tes kemampuan pemecahan masalah matematis. Hipotesis diuji dengan menggunakan uji t. Hasil penelitian menunjukkan kemampuan pemecahan masalah matematis siswa yang belajar menggunakan pendekatan RME lebih tinggi daripada siswa yang belajar menggunakan pembelajaran konvensional, dan kemampuan pemecahan masalah matematis siswa yang memiliki self-efficacy rendah yang belajar dengan menggunakan pendekatan RME lebih tinggi daripada yang belajar dengan menggunakan pembelajaran konvensional.